2000
DOI: 10.1002/1097-0215(20001020)90:5<256::aid-ijc2>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline improves the oxygenation and radiation response of BA1112 rat rhabdomyosarcomas and EMT6 mouse mammary carcinomas

Abstract: Tumor hypoxia can significantly impact the efficacy of cancer therapy. Pentoxifylline, a methylxanthine derivative, can improve oxygen delivery to tissues and is widely used in the treatment of peripheral vascular disease and various cerebrovascular disorders. In this article, we show that pentoxifylline, combined with oxygen breathing, significantly improves the radiation response of two experimental tumors in vivo through improved tumor oxygenation. We also demonstrate that pentoxifylline does not directly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…11 Morever, it has been reported that pentoxifylline can improve tumor oxygenation and radiation responses. 12 However, few radiosensitizers are available on the market due to the difficulty and high cost of large-scale production; thus, development of new radiotherapy agents is of scientific and clinical interest.…”
Section: Introductionmentioning
confidence: 99%
“…11 Morever, it has been reported that pentoxifylline can improve tumor oxygenation and radiation responses. 12 However, few radiosensitizers are available on the market due to the difficulty and high cost of large-scale production; thus, development of new radiotherapy agents is of scientific and clinical interest.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pentoxifylline on membranes may explain its effects on cell deformability, inhibition of neutrophils priming by TNF-␣, diminished adherence and aggregation, reduced superoxide production, and improved locomotor responses (22). The positive influence of pentoxifylline on the microcirculation and peripheral oxygenation led to applications of the drug in experimental radiotherapy to improve oxygenation and in restoring the radiobiological effectiveness of photon irradiation (23)(24)(25)(26). In these experiments, pentoxifylline was shown to diminish the incidence and severity of late radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI microimaging was performed before and after placing 10 nm CNT in glass capillaries at different intervals of 2,4,6 hours using scan parameters: TR/TE/flip angle = 750 ms/4.18 ms/25°, FOV/matrix size/spatial resolution = 2.6 x 3.4 cm/ 256 x 256/0.015 mm, and the inversion time (TI approximately 250 ms) set to null normal skin. Epidermis and hair follicle were measured as reported by Sharma et al (2010) [60].…”
Section: Characterization and Toxicity Of Swcnt And Mwcnt Carbon Nanomentioning
confidence: 99%
“…Initially, hypoxia induced by CNT was estimated by clonogenic assay of clonogenic cell survival [59][60][61]. Oxygen pressure measurement of poor oxygenation in tumor cells is other method of cytotoxicity testing.…”
Section: Characterization and Toxicity Of Swcnt And Mwcnt Carbon Nanomentioning
confidence: 99%